Peningkatan Pengrajin Sandal dalam Skala yang Lebih Besar dan Luas melalui Pengembangan dan Pemasaran Hasil Produksi UMKM Werdoro Waru Sidoarjo - Judiono Judiono; Mohammad Djaelani; Yayu Sri Wahyuni Hamzah; Ikhwanudin Ikhwanudin; Syaiful Anwar; Cilda Thesisa Ilmawan; Fahmy Ryadin; Soemardiono Soemardiono; Budi Handayani; Muhammad Yusron Maulana El-Yunusi; She Fira Azka Arifin; Adi Herisasono; Farid Zaini; Atmari Atmari (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Micro, small and medium enterprises (MSMEs) as one of the pillars of the nation's economy are able to face the big challenges of technological advances that are always running. Wedoro Village is one of the villages that maintains the Development and Marketing of Production Results in the Manufacture of sandals so that there are increasing sandal craftsmen who are always developing in this technological era. The method of implementing this service uses SWOT analysis, with the stages: preparation, implementation of activities, and evaluation. The target of this activity is all Sandal Craftsmen in Wdoro Waru, Sidoarjo. Supervisors carry out the role of guiding according to the expertise of their respective departments. The results of this activity are First, the improvement of Sandal Craftsmen; Second, the increasing interest of PkM practitioners to try new things